3D settlement analysis of underpinning piles under raft foundation subjected to nonuniform vertical loading - Kalpakcı, Volkan; Öztürk, Şevki; Murat Algın, Halil; Burak Ekmen, A. (Springer Verlag, 2018)
Existing rafts under the design loads sometimes experience excessive settlements or confront such a possibility in the future if the modified functionality of building is induced to increase the foundation loading. Differential settlement and deflection may also be observed in case of eccentric loading especially when these structures are built on soft soils. One of such precedents was observed in a silo structure used as a cement plant located in Douala, Cameroon. The structure that is founded on deep, soft clay with high ground water table rests on a raft supporting the storage tanks located at one side of the building conveying non-uniform loading to the existing raft. In one and a half year after completion of the construction, the silo structure had significantly settled and deflected. The underpinning pile remediation system allowing the continuity of cement production is applied from the outside of building using the rigidly connected protruding reinforced concrete section as a capping beam. In this study, the entire foundation system is numerically analyzed using the presented 3D finite element (FE) models. The back-analyses are used for the calibration concurring with the actual measurements of settlement and deflection at the site. The foundation systems with and without the underpinning piles are compared with each other to reveal how the remedial improvement is achieved by the presented underpinning pile system.
Keywords: Finite element; Raft; Settlement; Soft clay; Underpinning piles